2014
DOI: 10.1089/apc.2014.0194
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Antiretroviral Therapy Initiation in a Nationally Representative Sample of HIV-Infected Adults Receiving Medical Care in the United States

Abstract: Early antiretroviral therapy (ART) initiation reduces the risk of disease progression and HIV transmission, but data on time from HIV care entry to ART initiation are lacking. Using data from the Medical Monitoring Project (MMP), a population-based probability sample of HIV-infected adults receiving medical care in the United States, we assessed time from care entry to ART initiation among persons diagnosed , and persons without AIDS at care entry (HR 0.37; CI 0.31-0.43) had significantly longer times to ART i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The time to ART initiation for our overall cohort was 1.5 months, less than time to ART for HIV-infected persons with and without AIDS cited in other studies, 5 but greater than the target goal of less than 2 weeks to improve morbidity and mortality. Reasons for shorter time to ART initiation in our study sample may include the fact that outpatient referral from Grady Hospital is streamlined to a well-organized large Ryan White–funded clinic that is in close geographic proximity to GMH, and the clinic has a volume of HIV-positive patients cared for primarily by academic HIV providers who may be more likely than providers to implement guidelines recommending earlier ART initiation in other settings.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The time to ART initiation for our overall cohort was 1.5 months, less than time to ART for HIV-infected persons with and without AIDS cited in other studies, 5 but greater than the target goal of less than 2 weeks to improve morbidity and mortality. Reasons for shorter time to ART initiation in our study sample may include the fact that outpatient referral from Grady Hospital is streamlined to a well-organized large Ryan White–funded clinic that is in close geographic proximity to GMH, and the clinic has a volume of HIV-positive patients cared for primarily by academic HIV providers who may be more likely than providers to implement guidelines recommending earlier ART initiation in other settings.…”
Section: Discussionmentioning
confidence: 58%
“…4 Yet, median time to ART initiation for HIV-infected adults receiving medical care in the United States has been estimated as long as 10 months, with even longer times to initiation for African Americans, women, and persons living at or below the poverty level. 5 …”
Section: Introductionmentioning
confidence: 99%
“…38 Other studies have found disparities in time to ART initiation, with longer time to ART in blacks, uninsured, heterosexual women, MSM, and persons without AIDS. 39 Unlike treatment for other chronic conditions, such as CHF, cirrhosis, or chronic obstructive pulmonary disease, HIV treatment can lead to significant reversal of the main underlying illness. In fact, due to improvement in tolerability and recognition of long-term consequences of viral replication, ART is recommended for virtually all patients with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Yet time to ART initiation often remains suboptimal. 4,5 Many barriers exist that influence patients' ability to link, engage and be retained in HIV care, initiate ART, and achieve VS.…”
Section: Introductionmentioning
confidence: 99%